The Effect Of The Problem Based Flipped Classroom Learning Model On The Learning Outcomes Of Physics Students In Class Xi Mipa At SMA Negeri 1 Petang - I Gusti Ayu Era Anggreni Era; Ni Ketut Rapi; Dewi Oktofa Rachmawati (Jurnal Pendidikan Fisika Undiksha, 2023)
This study aims to analyze the differences in physics learning outcomes between students who study with the Problem Based Flipped Classroom Learning (PBFCL) model and students who study with the conventional learning model. This type of research is a quasi-experimental research with a pretest-posttest control group design. The research population is class XI MIPA SMA Negeri 1 Petang as many as 165 students. The sample selection was done by random assignment technique and obtained a total sample of 67 students. Data on students physics learning outcomes were obtained through the provision of essay tests with a test reliability of 0.893. The data obtained were analyzed by descriptive analysis and one-way ANACOVA. The results showed that the average value of student learning outcomes in the PBFCL model group and the conventional model were 87.75 and 78.95, respectively, with a standard deviation of 3.52 and 3.80. The conclusion of this study is that there are differences in student physics learning outcomes between students who study with the PFBCL model and students who study with the conventional learning model.